ANALISIS DAMPAK TRANSPORTASI OJEK ONLINE TERHADAP PENDAPATAN OJEK KONVENSIONAl DI KOTA JAMBI - Ferdila, Merdiana; Us, Kasful Anwar (Indonesian Journal of Islamic Economics and Business, 2021)
Transportation is the movement of people or goods from one place to another using a vehicle driven by humans or machines. Transportation is used to make it easier for humans to carry out their daily activities. One type of transportation in Indonesia is a motorcycle taxi. More and more ojegs are emerging. Along with the development of technology, conventional motorcycle taxis are starting to compete with online ojek transportation. The purpose of this study was to analyze the impact of online motorcycle taxis on conventional motorcycle taxis in Jambi city. The use of online motorcycle taxis, which are now widely used people, has resulted in reduced interest in using conventional ojek. The convenience offered by online ojek seems to drown out the existence of conventional ojek. The results showed that online motorcycle taxis had an impact on reducing the income of conventional motorcycle taxis. This research is expected to contribute to increasing knowledge in the world of education about the impact of the existence of online motorcycle taxis on conventional motorcycle taxi income.